2016
DOI: 10.1017/thg.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

Does Telomere Shortening Precede the Onset of Hypertension in Spontaneously Hypertensive Mice?

Abstract: Telomere length is widely considered as a marker of biological aging. Clinical studies have reported associations between reduced telomere length and hypertension. The aim of this study was to compare telomere length in hypertensive and normotensive mice at pre-disease and established disease time points to determine whether telomere length differs between the strains before and after the onset of disease. Genomic DNA was extracted from kidney and heart tissues of 4-, 12-, and 20-week-old male hypertensive (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
5
5
0
Order By: Relevance
“…Most of the studies that addressed this topic showed positive correlations between blood telomere length and telomere length in other tissues, such as muscle and liver, which suggests that blood telomeres can be a suitable surrogate marker for telomere length in at least some tissues [42,43,44]. Our findings showed a decline in rTL in mice with age which is in accordance with previous studies conducted on mice telomeres [32]. However, rTL in NMR did not shorten but rather showed a mild, significant elongation with age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of the studies that addressed this topic showed positive correlations between blood telomere length and telomere length in other tissues, such as muscle and liver, which suggests that blood telomeres can be a suitable surrogate marker for telomere length in at least some tissues [42,43,44]. Our findings showed a decline in rTL in mice with age which is in accordance with previous studies conducted on mice telomeres [32]. However, rTL in NMR did not shorten but rather showed a mild, significant elongation with age.…”
Section: Discussionsupporting
confidence: 92%
“…We analyzed relative telomere length (rTL) changes with age in blood DNA of 40 naked mole-rats and 31 mice in order to see if it differs between short-lived and long-lived animals. As expected, rTL decreased with age in mice (slope = −0.02343, F 1,29 = 7.741, p < 0.01, R = −0.459) (Figure 1A) [32]. Surprisingly, telomere length did not decrease with age in NMRs (Figure 1B), but rather showed a slight increase (slope = +0.01538, F 1,38 = 4.9691, p < 0.05, R = 0.34).…”
Section: Resultssupporting
confidence: 59%
“…Similarly, Tert protein levels increase after 3 wk of voluntary running in mice ( 57), but no differences were found in rats after 44 wk of exercise (33). In contrast, Terc is often relatively unchanged in animal models of heart disease (17,35,37), as it was in the present study. Despite these trends, there is still little evidence to suggest that these telomeric genes have the sensitivity and/or stable expression to identify CVD in its early and potentially reversible stages.…”
Section: Discussionsupporting
confidence: 52%
“…To the best of our knowledge, Table 1 presents a list of investigations that reported senescence in an established experimental model of hypertension or after exposure to prohypertensive stimuli. Overall, these studies generally indicate a pressuredependent association between increased cellular senescence and hypertension, 23,24 with angiotensin II being the predominant prosenescence factor. 25 Furthermore, antihypertensive therapy has been shown to reduce indices of senescence.…”
Section: Cellular Senescence Is a Widespread Phenotype In Hypertensionmentioning
confidence: 88%